Age-associated variation in the expression and function of TMEM16A calcium-activated chloride channels in the cochlear stria vascularis of guinea pigs - Zhou, Ying (Mol Med Rep, 2019)
The present study was designed to investigate the expression and function of transmembrane protein 16 (TMEM16A), a calcium-activated chloride channel (CaCC), in the stria vascularis (SV) of the cochlea of guinea pigs at different ages, and to understand the role of CaCCs in the pathogenesis of presbycusis (age-related hearing loss), the most common type of sensorineural hearing loss that occurs with natural aging. Guinea pigs were divided into the following groups: 2 weeks (young group), 3 months (youth group), 1 year (adult group), D-galactose intervention (D-gal group; aging model induced by subcutaneous injection of D-galactose) and T16Ainh-A01 (intraperitoneal injection of 50 µg/kg/day TMEM16A inhibitor T16Ainh-A01 for 2 weeks). Differences in the hearing of guinea pigs between the various age groups were analyzed using auditory brainstem response (ABR), and immunofluorescence staining was performed to detect TMEM16A expression in the SV and determine the distribution. Reverse transcription-quantitative PCR and western blot analyses were conducted to detect the mRNA and protein levels of TMEM16A in SV in the different age groups. Morris water maze behavior analysis demonstrated that spatial learning ability and memory were damaged in the D-gal group. Superoxide dismutase activity and malondialdehyde content assays indicated that there was oxidative stress damage in the D-gal group. The ABR thresholds gradually increased with age, and the increase in the T16Ainh-A01 group was pronounced. Immunofluorescence analysis in the cochlear SV of guinea pigs in different groups revealed that expression of TMEM16A increased with increasing age (2 weeks to 1 year); fluorescence intensity was reduced in the D-gal model of aging. As the guinea pigs continued to mature, the protein and mRNA contents of TMEM16A in the cochlea SV increased gradually, but were decreased in the D-gal group. The findings indicated that CaCCs in the cochlear SV of guinea pigs were associated with the development of hearing in guinea pigs, and that downregulation of TMEM16A may be associated with age-associated hearing loss.